PENERAPAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUKMENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SDN 25 PAKNING ASAL KECAMATANBUKIT BATU KABUPATEN BENGKALIS - Andriani, Andriani; Antosa, Zariul; Lazim. N, Lazim. N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract :This research aims to improve Mathematics learning outcomes fourth grade students of SDN 25 Pakning Asal Kecamatan Bukit Batu Kabupaten Bengkalis academic year 2014/2015. The improvement of studentsmathematics learning outcomes can be seen through the "Implementation Approach of Contextual Teaching And Learning (CTL)". This research was conducted in March 2015. The subject of this research were fourth grade studentls of SDN 25 Pakning Asal the number of students are 18 people consist of 8 boys and 10 girls.This research is classroom action research (PTK) was conducted in the classroom with two cycles. The instrument of this research is learning device consist of syllabus, lesson plan and worksheet. The instrument of data collection using a test in the form of observation sheet and results learning test. This thesis presents the results of studying the data obtained from the average results of study before action 59.44 rise 25.24% to 74.44 in cycle I. In the second cycle increased to 42.03% with an average of 84.44. The activities of teachers in the first cycle of the first meeting to obtain a percentage of 64.29% with the good category, at the second meeting has increased by 75.00% and the percentage of both categories. Furthermore, the third meeting of the second cycle of teacher activity also increased with the percentage of 85.71%, very good category and at the fourth meeting increased again with the percentage 92.86%, very good category. Activity of students in the first cycle of the first meeting of the percentage of 57.14% gain enough categories, at the second meeting has increased by 67.86% the percentage of both categories, the students begin to understand this cycle of learning activities by applying the contextual approach to teaching and learning (CTL) is characterized by activity of students in the second cycle third meeting increased with the percentage of 78.14% is very good category. From these results shown that the implementation approachof Contextual Teaching And Learning (CTL) can improve mathematics learning outcomes of fourth grade students of SDN 25 Pakning Asal Kecamatan Bukit Batu Kabupaten Bengkalis academic year 2014/2015.Keywords: Contextual Teaching And Learning (CTL), Mathematics learning outcomes.